Växtnäringsförsörjningen i ekologisk odling - Carlgren, Käll; Kirchmann, Holger (2004)
Yields, fertilization, fertilization efficiency, influence of soil quality and different crops on organic farming were discussed on a seminar held at the Royal Swedish Academy of Agriculture and Forestry (KSLA) in Stockholm in March 2004. totally comprising eleven speeches of organic fertilization, flows and leaching of nutrients. Also comparisons between organic and conventional farming were made on basis of field trials performed in north, central and south of Sweden. Shortly, you get lower yields of barley and wheat in organic farming than in conventional farming. Leys and even oats performed good yields in both systems. In order to get standard yields of wheat and barley you have to add manure, urine or other organic fertilizers approved by KRAV besides present soil nutrients. It was stated that KRAV fertilizers were less efficient than conventional mineral ones. A better accuracy and control of the access of soil N, P and K was asked for. A comparison between conventional and organic dairy production at the Ojebyn farm in north Sweden indicated that organic dairy can work if you are allowed to supply mineral food to the stock in order to compensate for the removal of P and other nutrients by milk and meat. The K-balance (added K minus removed K) was more negative in the organic treatments than in the convential ones. Soil weathering played an important role in clay soils to compensate for the K removal. The P-balance tended to be slightly negative both in conventional and organic systems and a small leaching of P was recognized in both systems. After fertilization for many years soil fertility and microbial enzyme activity was larger in organic treatments of a frame experiment. At last aspects on experimental difficulties and pitfalls you will meet when performing comparisons between organic and conventional farming were discussed.